The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
1986
DOI: 10.1007/bf00686083
|View full text |Cite
|
Sign up to set email alerts
|

Chronic manganese poisoning: A neuropathological study with determination of manganese distribution in the brain

Abstract: An autopsy case of a 52-year-old man suffering from chronic manganese poisoning (CMP) is reported with determination of the manganese distribution in the brain. The patient had been working in a manganese ore crushing plant since 1965. In 1967 he began to complain of difficulties in walking and diminished libido. Later, he developed various neuropsychiatric symptoms including euphoria, emotional incontinence, masked face, monotonous speech, "cock-walk", increased muscle tone, weakness of upper and lower extrem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
152
2

Year Published

1989
1989
2003
2003

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 312 publications
(165 citation statements)
references
References 18 publications
8
152
2
Order By: Relevance
“…Manganese neurotoxicity had previously been reported in miners after a prolonged exposure to manganese dust, resulting in extrapyramidal symptoms resembling Parkinson's disease (Yamada et al, 1986). In cirrhotic patients a high incidence of extrapyramidal symptoms is observed when a detailed and careful neurological evaluation is performed (Spahr et al, 1996).…”
Section: Relationship Between Brain Manganese Accumulation and Neurolmentioning
confidence: 99%
“…Manganese neurotoxicity had previously been reported in miners after a prolonged exposure to manganese dust, resulting in extrapyramidal symptoms resembling Parkinson's disease (Yamada et al, 1986). In cirrhotic patients a high incidence of extrapyramidal symptoms is observed when a detailed and careful neurological evaluation is performed (Spahr et al, 1996).…”
Section: Relationship Between Brain Manganese Accumulation and Neurolmentioning
confidence: 99%
“…Some speculation has suggested that the difference in neurobehavioral sensitivity of rodents and primates may be related to the fact that, unlike primates, rodents do not have pigmented substantia nigra, which is a brain region of relatively high Mn uptake. However, it appears that other nuclei of the basal ganglia are more likely to be target sites of Mn neurotoxicity (29 For improvement of the exposure assessment, the U.S. EPA has recommended obtaining personal exposure measurements using a probabilistic sampling design in areas where MMT is used in gasoline (96). At the time this recommendation was made, Canada was the only country where MMT was used in unleaded gasoline, and thus it was presumed that such studies would have to be conducted in Canada.…”
Section: Research Directionsmentioning
confidence: 99%
“…Postmortem examinations of Mn-exposed humans and experimental studies of Mnexposed laboratory animals indicate that Mn is distributed preferentially to nuclei of the basal ganglia, particularly the caudate, putamen, globus pallidus, subthalamic nucleus, and substantia nigra, and to a lesser extent to other regions of the brain, including the cerebellum and pituitary (29)(30)(31). Generally the primary sites of neuropathologic changes associated with Mn toxicity in humans and experimental animals are the basal ganglia, particularly the globus pallidus, caudate, and putamen.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Manganese-induced brain lesions tend to occur in regions of intense oxygen consumption (Yamada et al, 1986), and are marked by enhanced auto-oxidation and turnover of dopamine, losses of neurons and demyelination (Cotzias et al, 1971;Donaldson et al, 1984;Gerlach et al, 1994;Erikson et al, 1987). The site-specificity of the pathology and the selective targeting of dopamine have led to the comparison of manganese-induced neurodegeneration to that of other transition metals, iron and copper (Triggs and Willmore, 1984;Rauhala and Chiueh, 2000;Sengstock et al, 1993), i.e.…”
Section: Introductionmentioning
confidence: 99%